Lipoxins and aspirin-triggered lipoxin alleviate bone cancer pain in association with suppressing expression of spinal proinflammatory cytokines - Hu Shan (Journal of Neuroinflammation, 2012)
Abstract Background The neuroinflammatory responses in the spinal cord following bone cancer development have been shown to play an important role in cancer-induced bone pain (CIBP). Lipoxins (LXs), endogenous lipoxygenase-derived eicosanoids, represent a unique class of lipid mediators that possess a wide spectrum of anti-inflammatory and pro-resolving actions. In this study, we investigated the effects of intrathecal injection with lipoxin and related analogues on CIBP in rats. Methods The CIBP model was induced by intra-tibia inoculation of Walker 256 mammary gland carcinoma cells. Mechanical thresholds were determined by measuring the paw withdrawal threshold to probing with a series of calibrated von Frey filaments. Lipoxins and analogues were administered by intrathecal (i.t.) or intravenous (i.v.) injection. The protein level of LXA4 receptor (ALX) was tested by western blot. The localization of lipoxin receptor in spinal cord was assessed by fluorescent immunohistochemistry. Real-time PCR was carried out for detecting the expression of pro-inflammatory cytokines. Results Our results demonstrated that: 1) i.t. injection with the same dose (0.3 nmol) of lipoxin A4 (LXA4), lipoxin B4 (LXB4) or aspirin-triggered-15-epi-lipoxin A4 (ATL) could alleviate the mechanical allodynia in CIBP on day 7 after surgery. ATL showed a longer effect than the others and the effect lasted for 6 hours. ATL administered through i.v. injection could also attenuate the allodynia in cancer rats. 2) The results from western blot indicate that there is no difference in the expression of ALX among the naive, sham or cancer groups. 3) Immunohistochemistry showed that the lipoxin receptor (ALX)-like immunoreactive substance was distributed in the spinal cord, mainly co-localized with astrocytes, rarely co-localized with neurons, and never co-localized with microglia. 4) Real-time PCR analysis revealed that, compared with vehicle, i.t. injection with ATL could significantly attenuate the expression of the mRNA of proinflammatory cytokines (IL-1β and TNF-α) in the spinal cord in CIBP. Conclusions Taken together, the results of our study suggest that LXs and analogues exert strong analgesic effects on CIBP. These analgesic effects in CIBP are associated with suppressing the expression of spinal proinflammatory cytokines.